Examining the role of managerial assertiveness and self-confidence in enhancing employees' loyalty and productivity: A theoretical perspective - Isabirye, Anthony K.; Moloi, Kholeka Constance; Lebelo, Ramoshweu Solomon (Edelweiss Applied Science and Technology, 2025)
This study adopted a qualitative research design of a literature review genre to explore the theoretical underpinnings of the relationship between managerial assertiveness and self-confidence, and how they enhance employee loyalty and productivity. The review of the existing body of knowledge confirmed the link between managerial assertiveness, self-confidence, and their positive influence on employee loyalty and productivity. Assertive managers, who exhibit a strong sense of self-assurance and conviction in their decision-making, were found to inspire higher levels of trust, commitment, and engagement among their subordinates. This, in turn, fosters a sense of loyalty and motivation, leading to enhanced employee performance and productivity. Furthermore, the reviewed studies suggest that managerial self-confidence serves as a crucial catalyst in cultivating a positive work environment, where employees feel empowered, valued, and encouraged to contribute to the organization's success. Building on these findings, the study proposed strategies to promote managerial assertiveness and self-confidence, including targeted training programs, leadership development initiatives, and the creation of supportive organizational cultures. Theoretical implications and recommendations were provided to guide future research and inform managerial practices aimed at enhancing these crucial leadership attributes. Lastly, the study acknowledged the limitations of the literature review approach and suggested avenues for future empirical investigations to validate and expand the theoretical insights. The findings of this study provide a solid foundation for organizations seeking to optimize their human capital and achieve sustainable competitive advantage through the strategic development of assertive and self-confident managers.